A critical review on wire-arc directed energy deposition of high-performance steels - Kun Li; Wen Chen; Na Gong; Huayan Pu; Jun Luo; David Z. Zhang; Lawrence E. Murr (Journal of Materials Research and Technology, 2023)
Wire-arc directed energy deposition has the potential to revolutionize the production process of large-size components with faster deposition speeds at a lower cost. As the cornerstone of modern materials, steels, especially high-performance steels with properties such as corrosion, wear, and heat resistance, have increasingly been applied in wire-arc directed energy deposition. This paper provides a review of recent advancements in wire-arc directed energy deposition of high-performance steels, covering the microstructure, properties, and defect formation mechanism. Aiming at the properties of high-performance steels deposited by wire-arc directed energy deposition, such as thermal history and cooling rate. The comprehensive review had been introduced for the perspective what the simulation, analysis, and their composition with results and pre/in-situ/post-process for improving the properties of wire-arc directed energy deposition processed high-performance steels are then summarized. Finally, a systematic framework for performance optimization of wire-arc directed energy deposition high-performance steels is proposed. This review contributes to a better scientific understanding of the wire-arc directed energy deposition of high-performance steels and puts forward guiding opinions for the future work on high-performance steels manufacturing.